2003
DOI: 10.1038/sj.jp.7210944
|View full text |Cite
|
Sign up to set email alerts
|

Operational Evaluation of Pulse Oximetry in NICU Patients with Arterial Access

Abstract: These operational data suggest that with the methodology and devices currently in use, SpO(2) values in most all neonates who require arterial lines inaccurately correlate with measured arterial saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…Further, the data analytic approach is appropriate for our situation where the underlying true value measured is likely changing. Results are in agreement with previous studies suggesting that bias reported with first-generation pulse oximeters continue to be present in second-and third-generation devices and that inaccuracy at low saturations may be an inherent problem with the dual wavelength pulse oximeter [6,8] . This is further compounded by findings from a recent observational study suggesting that, even when alarm limit policies are implemented in the NICU, the desired SpO 2 remains outside the intended saturation range more than half of the time on average [15] .…”
Section: Discussionsupporting
confidence: 82%
“…Further, the data analytic approach is appropriate for our situation where the underlying true value measured is likely changing. Results are in agreement with previous studies suggesting that bias reported with first-generation pulse oximeters continue to be present in second-and third-generation devices and that inaccuracy at low saturations may be an inherent problem with the dual wavelength pulse oximeter [6,8] . This is further compounded by findings from a recent observational study suggesting that, even when alarm limit policies are implemented in the NICU, the desired SpO 2 remains outside the intended saturation range more than half of the time on average [15] .…”
Section: Discussionsupporting
confidence: 82%
“…The peak performance of the commercially available oximeters occurs in the range of 92% to 97%. 92 Therefore, in the critical range for oximetry screening (94% to 97%), the variability of the most commonly used oximeters should be negligible.…”
Section: Limitations and Challenges To Newborn Pulse Oximetry In Detementioning
confidence: 99%
“…The peak performance of the commercially available oximeters occurs in the range of 92% to 97%. 92 Therefore, in the critical range for oximetry screening (94% to 97%), the variability of the most commonly used oximeters should be negligible. CI indicates confidence interval; DORV, double-outlet right ventricle; HLHS, hypoplastic left heart syndrome; PA, pulmonary atresia; d-TGA, dextro-transposition of the great arteries; TAPVC, total anomalous pulmonary venous connection; Truncus, truncus arteriosus; TA, tricuspid atresia; AA/AS, aortic atresia/aortic stenosis; TOF, tetralogy of Fallot; AVSD, atrioventricular septal defect; CoA, coarctation of the aorta; and PS, pulmonary stenosis.…”
Section: Limitations and Challenges To Newborn Pulse Oximetry In Detementioning
confidence: 99%